Presurgical Nasoalveolar Molding of a Bilateral Cleft Lip and Palate Infant -Case Report - Ayşe Tuba Altuğ Ataç; Ümit K. Akal (Galenos Yayinevi, 2007)
The objective of presurgical nasoalveolar molding is to reduce the severity of the initial cleft deformity and to achieve better and more stable results in cleft lip and palate infants. This enables the surgeon to operate a cleft deformity that is of minimal severity with a better treatment outcome. In this case report, a bilateral cleft lip and palate infant who was treated with nasoalveolar molding prior to his primary lip and nose closure surgery is presented.